An Ecosystem Services Approach in Valuing Contribution of Agrosilvopasture to Household’s Income in Rural Area Central Kalimantan - Afentina; Yanarita; Tri Minarni; Yuliana (Postgraduate, University of Mataram, 2026)
Agroforestry is a sustainable land use system that provide wide range of ecosystem services, recommending solutions for biodiversity conservation, rural livelihood, and climate change adaptation. To be able to compete with large-scale monoculture plantations such as oil palm plantations, traditional agroforestry is required to provide better economic benefits to farmers. This research aimed to provide empirical evidence of role of agrosilvopature to rural livelihood by assessing provisioning services and economic contribution to household income. The Data collected from field observation included species component of agrosilvopasture, utilization, and economic value using market approach. The Analysis employed descriptive statistics. The research found three types of agrosilvopasture based on the livestock species: pig-based agrosilvopasture, goat-based agrosilvopasture and chicken-based agrosilvopasture. Agrosilvopasture provide various provisioning services including food, cooking spice, construction material, medicine, fodder and fertilizer. Income from agrosilvopasture provides a significant contribution to total farmer income, varying from 59% to 65%. In addition, agrosilvopasture assured sustainable income by providing weekly income, monthly oncome and long-term income. The study concluded that agrosilvopasture provide a variety of products to meet farmers' needs and a sustainable source of income. Studying agrosilvopasture components and how they contribute economically is important to increase adoptability and provide recommendations for decision-makers in developing strategies for rural development and ecological conservation.